2019
DOI: 10.3389/fphar.2019.00715
|View full text |Cite
|
Sign up to set email alerts
|

Natural Plants Compounds as Modulators of Epithelial-to-Mesenchymal Transition

Abstract: Epithelial-to-mesenchymal transition (EMT) is a self-regulated physiological process required for tissue repair that, in non-controled conditions may lead to fibrosis, angiogenesis, loss of normal organ function or cancer. Although several molecular pathways involved in EMT regulation have been described, this process does not have any specific treatment. This article introduces a systematic review of effective natural plant compounds and their extract that modulates the pathological EMT or its deleterious eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(115 citation statements)
references
References 274 publications
(278 reference statements)
3
111
0
1
Order By: Relevance
“…It has been reported that NPCs exhibit anticancer, anti-inflammatory and anti-fibrotic effects, which inhibits pathological EMT through different cell signal transduction pathways (10). In the present study, the expression of epithelial marker E-cadherin increased following CVB-D treatment, while the mesenchymal markers N-cadherin and vimentin decreased.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been reported that NPCs exhibit anticancer, anti-inflammatory and anti-fibrotic effects, which inhibits pathological EMT through different cell signal transduction pathways (10). In the present study, the expression of epithelial marker E-cadherin increased following CVB-D treatment, while the mesenchymal markers N-cadherin and vimentin decreased.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, bioactive natural components extracted from plants have received attention for their inhibition of epithelial-mesenchymal transformation (EMT) through anti-inflammatory, anti-fibrosis or anti-oxidant mechanisms (9). It has been demonstrated that pathological EMT is inhibited by NPCs via different cellular signal transduction pathways (10).…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin was extensively used as anticancer molecule in different studies and its efficiency was demonstrated both in vitro and in vivo. Considering different typologies of cancer, it is able to reduce the tumor size, growth rate, and vascularization, as described by Ahmed et al [116], Imran et al [117], and Avila-Carrasco et al [118] in recent reviews, mainly by a mechanism in which apoptosis of cancer cells is induced.…”
Section: Luteolinmentioning
confidence: 99%
“…14 Namely, during EMT, cancer cells undergo a series of changes (biochemical, morphologic and genetic) that allow them to have a more mesenchymal-like phenotype that is thought to be necessary to promote cancer cell migration and invasion, and their escape from the primary tumor. 14 Despite the fact that the search for compounds able to interfere with the EMT process has been increasing in the past years, it is still mainly based in the use of natural compounds isolated from plants, 15 while the use of metal-based compounds in this branch of medicinal chemistry remains poorly researched. In addition to targeting EMT, several of these metalbased compounds also aim to affect Reactive Oxygen Species (ROS) equilibrium 8,11,12,16 since ROS can act as signaling molecules in many cellular pathways, including those involved in tumor progression.…”
Section: Introductionmentioning
confidence: 99%